2021
DOI: 10.1002/brb3.2037
|View full text |Cite
|
Sign up to set email alerts
|

Cortical morphometric changes associated with completeness, level, and duration of spinal cord injury in humans: A case–control study

Abstract: Objective This study investigated how the injury completeness, level, and duration of spinal cord injury (SCI) affect cortical morphometric changes in humans. Methods T1‐weighted images were acquired from 59 SCI patients and 37 healthy controls. Voxel‐based morphometry analyses of the gray matter volume (GMV) were performed between SCI patients and healthy controls, complete SCI and incomplete SCI, and tetraplegia and paraplegia. Correlation analyses were performed to explore the associations between GMV and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Our study demonstrated gray matter atrophy in the bilateral thalamus, which was in accordance with previous VBM studies and meta-analyses ( 23 , 34 36 ). Although neurons in the brain are not disrupted directly following SCI, the afferent motor pathway and efferent sensory pathway undergo degenerative processes ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study demonstrated gray matter atrophy in the bilateral thalamus, which was in accordance with previous VBM studies and meta-analyses ( 23 , 34 36 ). Although neurons in the brain are not disrupted directly following SCI, the afferent motor pathway and efferent sensory pathway undergo degenerative processes ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 93%
“…Other VBM studies did not detect any brain alterations in SCI patients relative to the brains of healthy controls ( 21 , 22 ). Previous VBM study also uncovered that various clinical characteristics including injury level, severity, and duration can affect the brain alterations after SCI ( 23 ). In fact, most neuroimaging studies on SCI showed list of limitations including small cohort sizes (<20 patients), differences in patient characteristics (i.e., level and severity of injury), image acquisition, and post processing techniques, which may lead to inconsistent results and statistical inefficiency ( 4 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…SFG is involved in various cognitive and motor control tasks 65 , 66 , whereas IFG is involved in resolving the conflict between motor intention and sensory feedback 59 . Structural atrophy in these regions after SCI has been widely reported 14 , 21 , 46 . ACC is involved in the encoding of emotional information on pain and descending pain modulation 49 , and its structural atrophy is common in NP patients post-SCI 20 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…MFG is involved in executive function and emotional regulation 57 , 58 , whereas IFG is involved in resolving the conflict between motor intention and sensory feedback 59 . Many studies have reported the atrophy of GMV of MFG and IFG in SCI patients compared with the control 14 , 21 , 46 , 60 . Our previous publication has demonstrated that NT3/chitosan treatment can promote the recovery of motor function in animals 31 , and these structural alterations in motion-related brain regions may contribute to this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation